FIBER CLEANING PROCESS - Marg’uba Alisherova (Journals Park Publishing, 2024)
This article provides information about fiber and its quality indicators, and also explains in detail the ways to identify defects in the fiber composition.
Keywords: Fiber, quality, gin, defect, seed.